Aqueous and n-Hexane Fractions of Eruca sativa Differentially Target Glycemic Control and Pancreatic Islet Protection in Diabetic Rats - Nasution, Sri Lestari Ramadhani; Tamarin, Tamarin; Purba, Amelia Salsabila; Suhartina, Suhartina; Sihotang, Widya Yanti (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: The search for novel antidiabetic agents that simultaneously lower blood glucose and protect pancreatic β-cells is crucial. While Eruca sativa is known for its antidiabetic properties, the specific contribution of its solvent fractions to different therapeutic targets remains poorly understood. Therefore, this study was conducted to identify how different fractions selectively target glycemic control or pancreatic islet integrity.METHODS: Twenty-five male Wistar rats were rendered diabetic by a single intraperitoneal injection of 45 mg/kg streptozotocin. Diabetic animals were divided into five groups (n=5): diabetic control, positive control (0.45 mg/kg glibenclamide), and three treatment groups receiving n-hexane, ethyl acetate, or aqueous fractions of 400 mg/kgBW E. sativa for 14 days. Phytochemical screening was performed to identify bioactive profiles. Blood glucose was monitored periodically, and pancreatic tissues were assessed using a histopathological scoring system (0–4) and islet area measurement.RESULTS: Aqueous fraction showed the most potent antihyperglycemic activity, significantly reducing blood glucose (208.8±36.02 mg/dL) compared to the diabetic control (419.6± 117.11 mg/dL). Conversely, the n-hexane fraction provided superior pancreatic protection, maintaining the highest islet area (19,109.81±7,549.98 µm²) and the best histopathological score (2.8±0.8) among all treatment groups. Phytochemical screening revealed a distinct distribution of compounds, with flavonoids concentrated in the aqueous fraction and terpenoids in the n-hexane fraction.CONCLUSION: This study demonstrates that therapeutic efficacy of E. sativa is fraction-specific, driven by its distinct phytochemical profiles. The aqueous fraction is the most effective for rapid glycemic control, significantly reducing blood glucose levels. Conversely, the n-hexane fraction provides superior pancreatic protection, as evidenced by the highest islet area and improved histopathological scores. These findings suggest that E. sativa possesses a dual-target potential; while the aqueous fraction excels in antihyperglycemic action, the n-hexane fraction is more potent for pancreatic islet preservation. KEYWORDS: Eruca sativa, diabetes mellitus, histopathology, pancreatoprotective, solvent fractions, antihyperglycemic